Impact of Instrumental Support from Family on Medication Adherence among Tuberculosis Patients - Nursasi, Astuti Yuni; Huda, Mega Hasanul; Rahmasari, Syifa Widya (UI Scholars Hub, 2022)
Instrumental support is concrete and tangible, for instance, helping to provide food or accompanying patients to health care facilities. However, its impact on medication adherence among tuberculosis patients in Indonesia needs to be explored. This study aimed to examine the impact of instrumental support from family on tuberculosis patients’ adherence to medication in Bogor City, West Java Province, Indonesia. A cross-sectional study involving 106 participants with an age average of 39.7 (SD = 14.9) was conducted in 12 primary health care (PHC). The independent variables (age, sex, education, employment status, wealth index, and the distance between home and PHC) of instrumental support from family was assessed using MMAS-8. In contrast, the dependent variable of medication adherence was assessed using a self-reported instrument. Multivariate binary logistic regression was used in the analysis and indicated that participants receiving family support were more likely to adhere to medication protocol (95% CI = 1.1–6.3; p-value = 0.029). Instrumental support from family was associated with medication adherence among tuberculosis patients in Bogor City, West Java Province, Indonesia. It is necessary to design further comprehensive interventions in the community setting to encourage the family to support tuberculosis patients following medication protocol.